2017
DOI: 10.2106/jbjs.rvw.16.00091
|View full text |Cite
|
Sign up to set email alerts
|

Current Treatment Options for Glenohumeral Instability and Bone Loss

Abstract: * Management of recurrent anterior glenohumeral instability with bone loss is challenging and may necessitate osseous augmentation.* Glenoid and humeral-head osseous deficits should be managed simultaneously when there is severe bipolar bone loss. This is determined on the basis of the size of glenoid bone loss and/or Hill-Sachs lesion and the risk of engagement via the glenoid track concept based on the location and orientation of the lesion(s).* The quantification of glenoid bone loss and Hill-Sachs lesions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 90 publications
0
26
0
Order By: Relevance
“…Regarding the management of isolated critical humeral bone loss and no previous surgery, a consensus was reached across all subspecialties that a Bankart repair with or without remplissage would be performed. A critical review conducted by Provencher et al 63 established algorithms for treating different types of bone loss. The results of their review, as well as a systematic review and meta-analysis conducted in 2018 by Liu et al, 43 support our findings that combined Bankart repair and remplissage are appropriate for managing recurrent instability with humeral head bone loss of 20%-25% and subcritical glenoid bone loss.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the management of isolated critical humeral bone loss and no previous surgery, a consensus was reached across all subspecialties that a Bankart repair with or without remplissage would be performed. A critical review conducted by Provencher et al 63 established algorithms for treating different types of bone loss. The results of their review, as well as a systematic review and meta-analysis conducted in 2018 by Liu et al, 43 support our findings that combined Bankart repair and remplissage are appropriate for managing recurrent instability with humeral head bone loss of 20%-25% and subcritical glenoid bone loss.…”
Section: Discussionmentioning
confidence: 99%
“… 29 For bipolar lesions, this often necessitates a bony augmentation procedure, and with higher magnitudes of combined bone loss, both the humeral and glenoid sides need to be addressed. 26 , 60 , 63 , 84 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Historically, 20% to 25% has been accepted as the “critical” cutoff value at which glenoid bone loss should be reconstructed during surgery. 2 , 3 Due to the unsatisfactory results reported with isolated capsulolabral repair in athletes with recurrent glenohumeral instability and glenoid bone deficit >20%, most authors recommend glenoid reconstruction with bone grafting in these patients. 2 , 3 …”
mentioning
confidence: 99%
“…Additionally, it was previously described that MRI may underestimate the degree of glenoid bone loss as compared with CT; therefore, the bone loss measurements in the present scenario could represent a best-case scenario. 39 Last, this study observed statistically significant relative changes in the same shoulder with pre- and postinstability imaging. Therefore, while the absolute value of glenoid bone loss may be more accurately assessed in CT, the relative decrease in glenoid width was consistent with the MRI technique used.…”
Section: Discussionmentioning
confidence: 52%